Pengaruh Penerapan LKS Berorientasi Pendekatan Demonstrasi Interaktif untuk Meningkatkan Kompetensi IPA Fisika Siswa Kelas VIII SMPN 3 Lembah Gumanti - Khairun Nisa Al-yafasy; Akmam Akmam; Hidayati Hidayati (Universitas Negeri Padang, 2018)
Science competence of grade VIII students in junior high school 3 Lembah Gumanti has not shown optimal result. One solution that can be used to improve student’s science competence is by using teaching materials that support the learning process and assist students in developing their thinking skills. The teaching material used in this research is student worksheet oriented interactive demonstration approach. This type of research is Quasi Experiment with Randomized Control Group Only Design. The population of this research is students of grade VIII in junior high school 3 Lembah Gumanti which registered in the academic year 2016/2017. Sampling is done by Purposive Sampling technique. Research data includes knowledge competence, attitude and skills. The results of data analysis indicate that student worksheet oriented interactive demonstration approach gives a significant influence on the competence of knowledge and attitude but does not give a significant influence on skill competence.